2016
DOI: 10.1080/15389588.2016.1150591
|View full text |Cite
|
Sign up to set email alerts
|

Road traffic accidents and self-reported Portuguese car driver's attitudes, behaviors, and opinions: Are they related?

Abstract: Objective: This study aims to characterize Portuguese car drivers in terms of demographic characteristics, driving experience, and attitudes, opinions and behaviours concerning road traffic safety. Furthermore, associations between these characteristics and self-reported involvement in a road traffic accident as a driver in the last three years were analysed. A final goal was to develop a final predictive model of the risk of suffering a road traffic accident. Methods: A cross-sectional analytic study was deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…A study in Jordan also found that drivers with more driving experience were more exposed to crash risk and were often involved in crashes (4). The authors of an analytic study in Portugal (42), identified that 612 car drivers (37.3%) reported being involved in a road traffic crash with damage or injury in the period 2013-2016. The majority were male, older than 65 years old, with no children, not employed, and living in an urban area.…”
Section: Resultsmentioning
confidence: 99%
“…A study in Jordan also found that drivers with more driving experience were more exposed to crash risk and were often involved in crashes (4). The authors of an analytic study in Portugal (42), identified that 612 car drivers (37.3%) reported being involved in a road traffic crash with damage or injury in the period 2013-2016. The majority were male, older than 65 years old, with no children, not employed, and living in an urban area.…”
Section: Resultsmentioning
confidence: 99%
“…These differences maybe can be explained by the fact that Brazil is a developing country, and so regulatory measures appear to be more effective, contrary to what is found in some developed countries. However, other measures are identified as capable of positively impacting the reduction of accidents such as education campaigns (Bon de Sousa, Santos, Mateus, Areal, Trigoso, & Nunes, 2016), improvement of the road network, and traffic management (Sun, Liu, Chen, & He, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Their use as a marker for road safety in the present research is intuitive, logical and evidence-based. Several studies showed that a positive history of traffic violations is a good predictor of poor road safety or risky driving (Bon de Sousa et al, 2016;Evans, 1996;Iversen & Rundmo, 2004;Nabi et al, 2007;Parker, Reason, Manstead, & Stradling, 1995).…”
Section: Research Measuresmentioning
confidence: 99%